The Effect of Communication on Work Effectiveness - Dva Alqil Syuhada; Eva Nandha Jalma Yael; Natasya Machendrei Haliza Rachmadev; Rafinaxa Fathir Arisislam (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2023)
Communication is a part of human interaction activities. Effective communication has a direct effect on the results of work effectiveness. An intimate and open work atmosphere between colleagues, superiors, and subordinates is a step to achieve company and organisational goals. The purpose of this study is to determine the effect of communication on work effectiveness. This study used a qualitative method by collecting literature review data. The research results show that communication plays an important role in achieving work effectiveness in various contexts. Although there are variations in research results, there is a consensus that good and effective communication contributes to increased work effectiveness.